AKTIVITAS ANTIBAKTERIEKSTRAK MAKROALGA Padina australis DAN Laurencia nidifica DI KEPULAUAN SERIBU TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Yulneriwarni Yulneriwarni (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
Macro algae are plants that live in the sea, belongs to the group Thalophyta. These herbs contain bioactive compounds that have the potential in the health field that is antibacterial. Antibacterial substances used as drugs in the treatment of several diseases caused by bacteria. Type of macro-algae used in this study is Padina australis and Laurencia nidifica of Pulau Penjaliran TimurKepulauan Seribu, using bacteria Staphylococcus aureus and Escherichia coli as test bacteria. Antibacterial testing method used is the method of dilution with extract concentrations of 10%; 20%; 30%. For comparison is used as positive control in the form of chloramphenicol while the negative control used mueler hinton broth medium. The design used in this study is completely randomized design factorial. The results show extracts of P. australis and L. nidifica has potential as an antibacterial with different abilities to the test bacteria. L. nidifica extract has antibacterial power capability is higher than P. australis. Both types of macro-algae extract at a concentration of 10% is able to inhibit the growth of test bacteria E. coli and S. aureus. Test bacteria E. coli has a more sensitive response to both macro-algae extract when compared with S. aureus bacteria.